Pengembangan Aparatur berbasis Kompetensi di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu di Kabupaten Demak Provinsi Jawa Tengah - Dwi Ayu Sulistyaningrum; Ika Sartika; Gasper Liauw (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
This research is motivated by the duties and functions of an ASN to provide services to the community. The development of industrial revolution 4.0 currently impacts the government bureaucracy required to be professional, have integrity, and serve the community. Departing from the above thought, the authors are interested in researching with the title